Does innovation types moderate the relationship between organizational learning capability and technological innovation implementation in manufacturing process ? a proposed framework - Adam Mat; Razli Che Razak (Universiti Malaysia Kelantan, 2013)
The rapidly rising rate of technological change presents a lot of challenges and opportunities for organizations. Research has fairly established that technological innovation implementation is associated with organizational learning. However, few studies have investigated on the roles of innovation types : radical and incremental on the established relationship. It will focuses at implementation phase of innovation process, where innovation has be fully developed then it must be implemented. The issues of implementation is crucial in innovation research. Identification of success or failure of innovation can be done through implementation phase. Futhermore, the success of the technology implementation will determine whether any innovation is achieved its objective or not. This paper aims to investigate the framework types of innovations as moderating effects on the relationship between organizational learning capability and technological innovation implementation. The paper proposes that both innovation types enhance technological innovation implementation succes.